The Influence Of Promotion And Product Quality On Purchase Decisions Of Jofie Bakery & Cake Shop Products In Medan - Fachrozie, Ridho; Syahriza, Rahmi; Rahmani, Nur Ahmadi Bi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This study aims to investigate the impact of promotion and product quality on consumers' purchasing decisions regarding Jofie Bakery Cake Shop products in Medan. Quantitative research methods were employed for this study. Data analysis involved descriptive analysis and multiple linear regression analysis. The research encompassed respondent profiling, data variable descriptions, validity testing, including normality, multicollinearity, and heteroscedasticity tests, and hypothesis testing comprising multiple linear regression, R2 coefficient of determination, simultaneous F-test, and partial T-test. The findings revealed that while promotion does not significantly influence the purchasing decisions of Jofie Bakery Cake Shop products in Medan, product quality plays a significant role in shaping these decisions. This research suggests that Jofie Bakery Cake Shop should focus on enhancing its promotion strategies, expanding its reach, and considering collaborations with other entities to broaden its product visibility and consumer base.